PENERAPAN MODEL PEMBELAJARAN KOLABORATIF TIPE TEAMS-GAMES-TOURNAMENTS (TGT)S UNTUK MENINGKATKAN KETRAMPILAN MEMBACA TEKS BERBAHASA INGGRIS - Rosmita Ambarita; Juli Yanti Harahap (Jurnal Akrab Juara, 2018)
This study examines the application of one of the collaborative learning models of "Teams-Games-Tournaments (TGT)" to improve students' skills in reading English-language texts. The method used in this research is classroom action research method, by doing 2 actions in 2 cycles. Each cycle consists of 4 stages: planning, execution, observation and reflection. The result of the research shows that the results obtained from the students from giving the action for 2 cycles have increased. Keywords: Collaborative, TGT, Reading Skills